Webinar-based continuing medical education in otorhinolaryngology during the COVID-19 pandemic in Germany: a longitudinal study - Leif Erik Walther; Alexander Blödow; Stefan Volkenstein; Stefan Dazert; Jan Löhler (BMJ Open)
Objective Reliance on webinars for continuing medical education (CME) has increased since the onset of the COVID-19 pandemic. Here, we aimed to evaluate the teaching methods used in these webinars.Design Retrospective, longitudinal study.Setting 20 CME-approved webinars, conducted March–December 2020 in Germany, and lasting 2.25 hours each.Participants Otorhinolaryngologists pursuing CME credits.Interventions Postwebinar participant assessments of the speaker, effects on practical work, desired scientific content, technical quality, interactions, attention and future training behaviour.Results On average, 780 participants joined each webinar. The mean survey response rate was 35% (n=282). When asked how well the speaker had mastered the content, 38% responded ‘very well’, 44% responded ‘well’, 14% indicated ‘satisfactory’ and 4% chose ‘sufficient’. The frequency of webinars was considered appropriate by 92%, too high by 4% and too low by 4% of participants. The measured attention of the participants was 90%. After the COVID-19 pandemic lockdown, 68% of participants preferred online teaching. The average costs per participant were €3.50 (about $4.25 or £3.15) per webinar.Conclusions Although the pandemic context likely influenced the results, we conclude that periodic ear, nose and throat webinar training during COVID-19 in 2020 was an effective alternative delivery method. We found high attention rates, high levels of participant satisfaction and low costs. Evaluations and re-evaluations will be necessary to adapt teaching concepts successfully and ensure high levels of teaching and learning efficiency.